Synthesis and characterization of yttria and scandia co-doped zirconia as solid electrolyte - Villanueva, Matthew Bryan P.
Electrolytes used for solid oxide electrolysis cell (SOEC) technology must be dense and have high ionic conductivity. Electrolytes with high enough conductivities are being explored for intermediate temperature applications. In addition, lowering processing time and temperature of the electrolyte material could provide cost benefits to manufacturing. In the current study, an all-solid alkoxide sol-gel method is used to synthesize ZrO2 (zirconia) with Y2O3 (yttria) and SC2O3 (scandia) at dopant levels of 4 mol % and 8 mol %. Zirconia was also co-doped with yttria and scandia at equal proportions and at 8 mol % total dopant level to study the effect on crystal structure and electrochemical performance. From the results of TGA, a weight loss of ~25-27 % was observed at 600°C. No further weight loss was observed above 600 degree celsius. FTIR analysis of powder specimens showed that the functional groups identified were linked to residual alcohols and nitrogen compounds. These functional groups were eliminated only after calcination at 600°C. XRD of calcined powder specimens showed the following: (1) the 4 mol %, 8 mol %, and the co-doped powder specimens were indexed as cubic, and; (2) crystallite sizes vary from 60-1008. Upon sintering at 1200°C for 5h, 4YSZ, 4ScSZ, 8YSZ, 8ScSZ, and 4Sc4YSZ ceramics had relative densities of 94.7 %, 95.6 %, 96.1 %, 97.4 %, and 98.3 %, respectively. The sintered specimens showed the following crystal structure from XRD: (1) at 4 mol %, the specimens were indexed as mixed cubic and tetragonal, while; (2) the 8 mol % specimens including the co-doped specimen were observed to have the cubic phase. SEM also revealed that grain sizes of 4 mol % specimens are 0.2 microns, and that of 8 mol % specimens are 0.2 1.8 microns. Nyquist plots of sintered specimens showed both grain interior (GI) and grain boundary (GB) impedance from 300-450°C. From 500-700°C, a single arc is observed and is attributed to the total electrolyte impedance. In the 500-700°C range, the activation energy (Ea) of 4 mol % specimens were relatively higher than the 8 mol % specimens. Within the 8 mol % dopant systems, Ea trend is Ea/4Sc4YSZ > Ea/8Scsz > Ea/8YZYS. At 700 degree celsius, conductivities of 4YSZ, 4ScSZ, 8YSZ, 8ScSZ, and 4Sc4YSZ were 2.44 x 10-2, 1.65 x 10-1, 3.35 x 10-2, 1.57 x 10-1, and 1.09 x 10-1 Scm-1, respecti